Analisis Implementasi Kebijakan Perizinan Pemanfaatan Sumber Daya Air di Balai Besar Wilayah Sungai (BBWS) Cimanuk Cisanggarung - Cindy Aulia Rahmadina; Siti Khumayah; Rahmayanti (Jurnal Ilmiah Publika, 2024)
This study analyzes the implementation of water resource utilization licensing policies at the Cimanuk Cisanggarung River Basin Organization (BBWS Cimanuk Cisanggarung). The research was conducted through a 10-week Research and Practice (Ristik) program using direct observation, interviews, and documentation methods, applying a qualitative descriptive approach based on the theoretical framework of Edward III (1980), which states that the success of policy implementation is influenced by four key variables: communication, resources, disposition, and bureaucratic structure. The findings identify a major issue: a significant number of water resource utilization activities are carried out without official permits. This problem is linked to the lack of oversight by authorized parties and the insufficient dissemination of information regarding licensing obligations. The study proposes four comprehensive solutions: (1) strengthening communication strategies through continuous public outreach; (2) increasing the capacity and number of human resources; (3) fostering a proactive attitude among policy implementers; and (4) improving bureaucratic structures to support better coordination and supervision. The conclusion highlights that the implementation of water resource utilization licensing policies still faces several challenges, particularly related to the low level of public compliance with licensing regulations